Assessment of Nutritional Status of Queens College Students of Lagos State, Nigeria - Akinyemi, O.; Ibraheem, A.G. (Pakistan Journal of Nutrition, 2009)
Malnutrition is a major public health and social problems among secondary school students in Nigeria. The study focuses on the assessment of nutritional status of 40 Queens College Students of Lagos State age 10-19 years. It was glaringly shown that most of the nutrients are lacking with inadequate energy intake especially among students of younger ages.